Wage insurance within German firms: do institutions matter? - Nicole Guertzgen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Using a large linked employer-employee data set, this paper studies the extent to which employers insure workers against transitory and permanent firm-level shocks. Particular emphasis is given to the question of whether the amount of wage insurance depends on the nature of industrial relations. Adopting the identification strategy proposed by Guiso et al. (2005), it is shown that wage insurance is particularly apparent for individuals subject to collective wage agreements. While collective contracts alone are sufficient to fully insure workers against transitory shocks in small plants, they provide only partial insurance in medium-sized and large plants. At large employers, the joint existence of collective contracts and works councils helps to provide full insurance against transitory shocks, but provides only partial insurance against permanent shocks. This finding is consistent with the amount of insurance against permanent shocks being constrained by the possibility of considerable job losses and bankruptcy.
Keywords: J31; J51; 330; Wage insurance; linked employer-employee data; collective bargaining; Tariflohn; Verdienstausfall; Arbeitsbeziehungen; Tarifpolitik; Betriebsrat; Produktivität; Schock; Betriebsgröße; Deutschland